Status of “ZELENOGRAD” storage ring - Arbuzov, V.; Chernov, K.; Chernyakin, A.; Churkin, I.; Dovzhenko, B.; Gorniker, E.; Kondakov, A.; Kozak, V.; Krutikhin, S.; Kulipanov, G.; Kuper, E.; Kuptsov, I.; et al. (Вопросы атомной науки и техники, 2008)
In 2000, after a long break, works on creation of a technological storage ring complex (TSC) have been renewed in ZELENOGRAD. TSC was developed at Budker INP of Siberian Branch of Russian Academy of Science. It consists of a linear accelerator on the electron energy up to 80 MeV, a small storage ring on the energy 450 MeV, a main storage ring on the energy 2 GeV and two electron transfer lines (TL-1 and TL-2). The Main Ring (MR) with energy of electrons 2 GeV is the dedicated synchrotron radiation source intended for the decision of problem of submicron technologies and realization of various researches in a range of wavelengths of 0.2…2000 Å. Linac was mounted and put into operation during 2000-2002. The circulating electron current was received in small storage ring in 2005. Currently, the assembling of TL-2 is being completed. The inspection of the main storage ring equipment made before is carried out. Besides, a modification of all control and power supply system MR is done and a modern electronic element base will be introduced. The status and the nearest planes concerning TSC main storage ring are described. У 2000 р. після довгої перерви відновилися роботи по створенню технологічного накопичувального комплексу - ТНК, у м. Зеленограді. ТНК був розроблений в ІЯФ СВ РАН. Він складається з лінійного прискорювача (ЛП) на енергію до 80 МеВ, малого накопичувача (МН) на енергію 450 МеВ, основного великого накопичувача (ВН) на енергію 2,2 ГеВ і двох каналів перепуску (ЕОК-1 й ЕОК-2). Накопичувач електронів з енергією електронів Е = 2,2 ГеВ є спеціалізованим джерелом СВ, призначеним для вирішення проблем субмікронних технологій, а також для проведення досліджень у проміжку довжин хвиль 0.2…2000 Å. Лінійний прискорювач був змонтований і запущений протягом 2000-2002 р. У 2005 р. був отриманий циркулюючий струм електронів у Малому накопичувачі. У цей час закінчується монтаж ЕОК-2. Проводиться ревізія устаткування ВН. Крім того, проводиться модернізація всіх систем керування і живлення і перехід на сучасну елементну базу. Описується статус ТНК і найближчі плани по монтажу і запуску ВН. В 2000 г. после долгого перерыва возобновились работы по созданию технологического накопительного комплекса – ТНК, в г. Зеленограде. ТНК был разработан в ИЯФ СО РАН. Он состоит из линейного ускорителя (ЛУ) на энергию до 80 МэВ, Малого накопителя (МН) на энергию 450 МэВ, основного большого накопителя (БН) на энергию 2.2 ГэВ и двух каналов перепуска (ЭОК-1 и ЭОК-2). Накопитель электронов с энергией электронов Е = 2.2 ГэВ является специализированным источником СИ, предназначенным для решения проблем субмикронных технологий, а также для проведения исследований в области длин волн 0.2…2000 ангстрем. Линейный ускоритель был смонтирован и запущен в течение 2000-2002 г. В 2005 г. был получен циркулирующий ток электронов в Малом накопителе. В настоящее время заканчивается монтаж ЭОК-2. Проводится ревизия оборудования БН. Кроме того, проводится модернизация всех систем управления и питания и переход на современную элементную базу. Описывается статус ТНК и ближайшие планы по монтажу и запуску БН.